Analysis of the Markowitz Method and the Single Index Method in Determining the Optimal Portfolio - Dhea Eka Fitriyani (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Investors generally make investments to get the maximum return with minimal risk. The optimal portfolio is a method that can be used to determine the stock portfolio that produces the maximum return with the least risk. The purpose of this study is to determine the accuracy of the Markowitz method and the single index method in determining the optimal portfolio and to determine whether or not there are differences in the results of optimal portfolio calculations using the Markowitz Method and the Single Index Method. The study population includes LQ-45 companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling method used in this study was purposive sampling, based on predetermined criteria obtained from 18 sample companies. The method used is the One-Sample t-Test and the Independent Sample t-Test. The results of this study indicate that there is no difference between the Markowitz Method and the Single Index Method in determining the Optimal Portfolio.